Combination thymosin alpha 1 and lymphoblastoid interferon treatment in chronic hepatitis C. Issue 5 (November 1996) - Rasi, G; DiVirgilio, D; Mutchnick, M G; Colella, F; Sinibaldi-Vallebona, P; Pierimarchi, P; Valli, B; Garaci, E
Abstract : BACKGROUND: Monotherapy for chronic hepatitis C using interferon (IFN) results in a very small proportion of patients exhibiting a sustained response. Clinical trials assessing the benefit of combination drug therapy may provide evidence of improved treatment response over that seen with single drug treatment. AIM: To assess the response in patients with chronic hepatitis C to one year of combination treatment: thymosin alpha 1 (T alpha 1), 1 mg twice weekly, and lymphoblastoid (L)-IFN, 3 MU thrice weekly. PATIENTS AND METHODS: Fifteen patients with serum HCV RNA positive chronic hepatitis C were studied. Eleven patients were treatment naive and four had failed previous standard IFN therapy. Thirteen patients were HCV RNA serotype 1b. All patients were given combination T alpha 1 and L-IFN therapy for one year with a six month follow up period. RESULTS: Six months after initiation of treatment seven patients (47%) were sera HCV RNA negative and at completion of the one year treatment 11 (73%), including two who had failed previous standard IFN treatment, had negative serum HCV RNA. Six months after treatment, six patients (40%), including five with HCV type 1b, showed a sustained response characterized by a negative serum HCV RNA. CONCLUSIONS: The results of this open label trial suggest that there may be a potential benefit to combining an immune modulator (T alpha 1) with an antiviral (IFN) in the treatment of chronic hepatitis C. Verification of the observations in this study require completion of a randomised controlled study.